ELEVATED TRIGLYCERIDE GLUCOSE INDEX IS RELATED TO THE PRESENCE OF HEART FAILURE - Sara Çetin Şanlıalp; Gökay Nar; Mehmet Güven Günver (İstanbul Tıp Fakültesi Dergisi)
Objective: Previous studies have shown a significant associa tion between insulin resistance (IR) measured by using different methods and heart failure (HF). In recent years, the triglyceride glucose (TyG) index has been used to measure IR, and there are several reports showing that the TyG index indicates conditions such as metabolic syndrome (MetS) and atherosclerotic process. However, there is no study investigating the association of the TyG index with HF. Therefore, we aimed to evaluate the role of the TyG index in HF presence and its relationship with HF severity in this study. Material and Method: Sixty-nine subjects matched for age and gender were analyzed retrospectively. The TyG index was used to measure IR and was calculated by the formula Ln [fasting triglycerides (mg/dl) x fasting glucose (mg/dl)/2]. The severity of HF was assessed by New York Heart Association (NYHA) functional class, left ventricular ejection fraction (LVEF) and N- terminal prohormone brain natriuretic peptide (NT-proBNP). Results: HF patients had higher TyG index (9.11±0.59 vs. 8.55±0.55; p<0.001) but there was no correlation between TyG index with HF severity identified by NYHA functional class, LVEF and NT-proBNP. The ROC curve showed the cut-off point of the TyG index in determining HF as 9.19 with 71% sensitivity and 51% specificity (AUC:0.745, p<0.001). Conclusion: TyG index may be a useful marker for diagnosis of HF, but is not correlated with HF severity.